Automatyczne nadzorowanie procesu szlifowania wgłębnego kłowego. - Leżański, Paweł (Wydawnictwo Politechniki Łódzkiej, 2012)
W pracy przeprowadzono teoretyczno-doświadczalna analize procesu szlifowania wgłebnego kłowego jako obiektu nadzorowania celem opracowania ogólnych zasad i wytycznych dla automatycznego inteligentnego nadzorowania tego procesu. Zostały przeprowadzone rozważania w trzech podstawowych grupach zagadnień. Po pierwsze przeanalizowano teoretyczno-doświadczalne podstawy nadzorowania procesu szlifowania wgłębnego kłowego. Następnie doświadczalnie sprawdzono przydatność wybranych miar wielkości procesowych do pełnienia funkcji symptomów określonych stanów i wyników procesu. Trzecia grupa zagadnień związana jest z budowa modelu procesu i wykorzystania go do klasyfikacji stanu procesu.Ustalono, że podstawa prowadzenia nadzorowania procesu powinien być tzw. zalecany obszar szlifowania. Określa on parametry procesu i jakości przedmiotu szlifowanego, które powinny być objęte nadzorowaniem. Zaliczono do nich: makro- i mikrozużycie CPS, drgania samowzbudne, uszkodzenia cieplne WW przedmiotu szlifowanego oraz chropowatość powierzchni szlifowanej. Przeprowadzona analiza zjawisk i procesów powiązanych z tymi wielkościami pozwoliła ustalić warunki zrealizowania automatycznego nadzorowania procesu dotyczące układów monitorowania i zastosowania metod identyfikacji stanu i wyników procesu. Badania doswiadczalne1 objęły pomiary bezpośrednich miar stanu CPS i jakości przedmiotu szlifowanego oraz miar wielkości procesowych wyznaczonych do nadzorowania. Jako przydatny do nadzorowania makrogeometrii CPS uznano sygnał drgań lub sygnał wartości skutecznej EA. Przy nadzorowaniu mikrogeometrii CPS i chropowatości należy wziąć pod uwagę siłę szlifowania i sygnał EA. Natomiast do nadzorowania uszkodzeń cieplnych WW przedmiotu szlifowanego wystarczająca jest znajomość wartości wskaźnika Bp. W celu uzyskania symptomów stanu procesu konieczne jest zastosowanie metod przetwarzania sygnałów, takich jak transformata Fouriera, transformata falkowa lub wyznaczanie miar statystycznych. Wyniki badan teoretycznych i doświadczalnych wykorzystano do budowy klasyfikatora stanu procesu w oparciu o zastosowanie teorii zbiorów przybliżonych rozszerzonej o relacje dominacji2. Otrzymane w wyniku przeprowadzonej klasyfikacji regułowe modele procesu umożliwiają dokonywanie skutecznej oceny jego stanu na podstawie wielu miar uzyskiwanych z różnych sygnałów pomiarowych. Stanowią one gotowa regułową bazę wiedzy o procesie szlifowania wgłębnego kłowego, która może być podstawa systemu eksperckiego tego procesu służacego do oceny i diagnostyki jego nowych realizacji, a także do ustalania wartości wybranych wielkości procesowych w celu osiągnięcia założonych wyników procesu.

In the work, theoretical and experimental analysis of the external cylindrical plunge grinding process as a supervision object is made to work out general rules and recommendations for automatic intelligent supervision of this process. The problem is considered in the three main groups of issues. Firstly, theoretical and experimental analysis of the external cylindrical plunge grinding process is made. Next, usefulness of selected features of the measured process variables to be symptoms of process states and results is experimentally verified. The third group of issues is related to development of a process model and its use in process state and result classification. After literature study and theoretical analysis of the process, it is established that to identify the incorrect states of the process, an acceptable working area has to be known. This area is delimited by a dynamic stability limit for small values of the specific material removal rate and by a burn and other thermal damage constraint for higher values of it. Additionally this area is narrowed down by a restriction resulting from the required surface roughness, the allowable normal force and the allowable work speed. This decides on process and workpiece quality parameters to be supervised. The type of wheel wear, the state of wheel macro- and micro-geometry, the state of thermal damages and the workpiece roughness are recognized as such parameters. Carried out analysis of phenomena and processes related to these parameters allows the condition for process monitoring, signal processing and feature extraction to be established. Experimental research consists of grinding tests encompassing on-line and off-line measurements. The cutting forces, vibration, the raw and RMS value of the acoustic emission signals are the on-line measurements of process variables during each grinding test. The profile and waviness of the grinding wheel cutting surface and the workpiece roughness are the off-line measurements of quantities directly characterizing the wheel state and the workpiece surface quality after every second test. The state of workpiece thermal damages is determined on the basis of the index expressing value of heat flux density entering the workpiece. The FFT procedure, the wavelet transform and statistical analysis are used for feature extraction from the measured signals. The utilized signal features are selected on the basis of literature study as well as on theoretical and experimental analysis. As a result, every process case is characterized by 17 process state features representing different types of process phenomena related to the process limitations and 5 quantities belonging to important process results: the type of wheel wear, the state of wheel makro- and micro-geometry, the state of thermal damages and the workpiece roughness. Next, the Dominance-based Rough Set Approach (DRSA) is proposed as a methodology for development of a process model and its use in process state and results classification. The DRSA allows for the extracting of knowledge hidden in the experimental data by the induction of the set of rules which creates a model of the grinding process. After an iterative feature selection procedure the induction of rule sets for each process result are conducted using the VC-DomLEM algorithm. Following this, the induced sets of rules are evaluated using the leave-one-out method. The induced rule model of the process allows all the example grinding cases gathered during the tests to be classified according to the original classes determined for the 5 different criteria of the process evaluation and it can be used for the classification of new process cases. So it can be employed as a knowledge base of an expert system for the external cylindrical plunge grinding process state evaluation and diagnosis.
Automatic supervision of external cylindrical plunge grinding.
Keywords: sanding; szlifowanie; szlifowanie wgłębne; szlifowanie kłowe; nadzór automatyczny; diagnostyka procesów przemysłowych; szlifowanie wgłębne kłowe; metoda przetwarzania sygnałów